The Income Elasticity of the Poverty Line - Kilpatrick, Robert W. (The Review of Economics and Statistics, 1973)
COMPARISONS of the extent of poverty at different times are greatly affected by whether the dividing line between the poor and the rest of the population changes as average income grows over time, and if so to what degree.1 The absolute income standard and the relative income standard are polar hypotheses about the income elasticity of the poverty line. Under an absolute standard of poverty, the poverty line is constant (in deflated dollars). In terms of what people thought of as poverty a century ago, the absolute standard implies that today almost no one is poor in the United States. Under a relative standard of poverty, the poverty line changes in the same proportion as average income if the relative income distribution is constant. The relative standard implies that if the shape of the income distribution is the same today as a century ago, the poverty problem is now no less.2 Probably more likely than either of these extremes is that people's judgment about the dividing line between poverty and a more adequate standard of living is determined by a mixture of concerns over both absoluteand relative conditions.3 If so, growth in average income increases the poverty line, but by less than in the same proportion. This proposition -that the income elasticity of the poverty line is between zero and one-is the hypothesis tested in this paper. I Time Series Analysis of Gallup Poll Results